Optimalisasi Tata Kelola dan Peningkatan Komitmen Organisasi: Studi Pada Pelatihan Kepemimpinan di PCIM Malaysia - Wiyadi; Muhammad Sholahuddin; Sarjito; Rara Yuni Rahmawati; Sisca Dian Rahmawati (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Muhammadiyah, as an Islamic movement with a moderate and cosmopolitan vision, faces unique challenges in managing ethnic, cultural and religious diversity in various countries. The leadership of the Special Branch of Muhammadiyah (PCIM) in Malaysia, which oversees 10 Special Branch Leaders of Muhammadiyah (PRIM), faces obstacles in organizational commitment and governance. To overcome this, PKM-KI UMS proposed a solution through three training programs: Achievement Motivation Training, PDCA Training, and Islamic Leadership Training, with a focus on developing leadership modules. This program aims to increase organizational commitment and governance in PCIM and PRIM Malaysia, as well as strengthen the Muhammadiyah community in Malaysia in facing organizational governance challenges and promote Muhammadiyah's moderate and cosmopolitan vision amidst socio-cultural dynamics across nations and countries. Program methods include initial surveys, needs analysis, training design, evaluation, and program sustainability. The program results show that leadership training can significantly increase commitment and effectiveness of organizational governance. This program provides new insights into the importance of leadership training that focuses on aspects of Islamic motivation, management and leadership in the context of cross-cultural organizations.